2018
DOI: 10.1016/j.evalprogplan.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Trying to bridge the worlds of home visitation and child welfare: Lessons learned from a formative evaluation

Abstract: Young children in families contacting the child welfare system are at high risk of recurrent maltreatment and poor developmental outcomes. Home visitation programs to support parenting may offer hope as a preventive resource but these programs are rarely linked with child welfare. This article describes findings from a formative evaluation of a program designed to connect child welfare-involved families to an existing evidence-supported home visitation program. The program, Early Childhood Connections (ECC), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Further, the literature on termination of telepractice services is scant. Reports within the home visitation literature note that changes in family status including returning to work, multiple competing appointments, or other scheduling barriers often lead families to discontinue services (Jack et al., 2016; Stahlschmidt et al., 2018). Likewise, changing a provider has been noted as a barrier for continuing services in both the home visitation and mental health literature (Beasley et al., 2018; Newman et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the literature on termination of telepractice services is scant. Reports within the home visitation literature note that changes in family status including returning to work, multiple competing appointments, or other scheduling barriers often lead families to discontinue services (Jack et al., 2016; Stahlschmidt et al., 2018). Likewise, changing a provider has been noted as a barrier for continuing services in both the home visitation and mental health literature (Beasley et al., 2018; Newman et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Home visitation is a service model, generally focused on parenting of children birth to 3 years, that seeks to support families in better understanding and responding to the developmental needs and skills of young children (Stahlschmidt et al., 2018). In the standard model of home visitation, a provider enters the family's home to offer developmental assessment, parent coaching, and family support.…”
Section: Introductionmentioning
confidence: 99%
“…Loman et al (2009) suggest that the low acceptance rate may also be related to who is initiating contact with the family (CPS instead of a community provider), how they explain the reason for contact, and how they present the services offered. Related child welfare studies have found that families reported to CPS are amenable to voluntary services from other agencies when engagement is made easier (Stahlschmidt et al, 2018). This difficulty to engage clients is likely associated with the stigma attached to CPS agencies, which needs to be addressed (Allan et al, 2018; Kemp et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Home visiting and regular contact with a case worker improved engagement in a supported housing programme for families with both child protection concerns and unstable living arrangements (Farrell et al, 2012). Families were more receptive to home visiting and home-based delivery of services in a study of Early Childhood Connections (ECC), a service integration process attempting to coordinate an evidence-supported home visiting programme with usual child welfare care (Stahlschmidt et al, 2018).…”
Section: Enablersmentioning
confidence: 99%